Post-disaster impacts on food security and nutritional demands of vulnerable groups - Basyigit, Bulent; Karimidastjerd, Atefeh; Cetinkaya, Turgay; Zeynep Bakkal, Leman; Basdogan, Hakan; Elmas, Negin; Azarabadi, Negin; Basdogan, Sinem; Toker, Omer Said (IOP Publishing Ltd, 2025)
This review examines the impact of disasters on food security and nutritional needs, with a focus on vulnerable populations. It highlights the nutritional challenges encountered by vulnerable groups, such as lactating women, infants, and the elderly. Disasters trigger acute stress responses that disrupt metabolic rates, inflammation, and tissue repair, creating a mismatch between emergency food supplies and physiological needs. Research highlights both immediate food insecurity and long-term health risks, such as increased obesity rates among evacuees. Older adults require sufficient protein intake to prevent muscle loss, yet evacuation shelter meals often lack essential nutrients. Dietary modifications, such as soft foods, can help address these needs, while emergency diets must also provide adequate vitamins and minerals to mitigate stress, immune dysfunction, and prolonged inactivity. Intervention programs, such as targeted food assistance, have positively impacted food security and nutritional outcomes. Sustainable approaches-like resilience frameworks and local food production initiatives-enhance long-term food security, particularly in resource-limited settings. Additionally, broader perspectives on food sovereignty and health equity emphasize the importance of addressing systemic inequities in food access. Strengthening local control over food resources and governance can improve resilience and food security during disaster recovery. The relationship between displacement, housing instability, and food insecurity further underscores the necessity of coordinated, multi-sectoral interventions. A comprehensive strategy should integrate both short-term emergency food provisions and long-term nutritional planning. This approach must incorporate quantitative data (e.g., household surveys, statistical models) and qualitative insights on community resilience to develop targeted, effective interventions. By adopting an integrated recovery framework, food security efforts can better meet the needs of vulnerable populations, fostering sustainable, long-term resilience in disaster-prone areas.
Keywords: post-disaster; nutrition management; food shortage; dietary habbits; vulnerable groups; food aid packages; EAST JAPAN EARTHQUAKE; CLIMATE-CHANGE; PUBLIC-HEALTH; DISASTERS; DISEASES; CHILDREN; Environmental Sciences & Ecology